2022
DOI: 10.1038/s41598-022-13639-7
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study to measure oil recovery factor by chemical agents and carbon dioxide after waterflooding

Abstract: Development of tight formations would be one of the main priority for petroleum industries due to the enormous demand to the fossil fuels in various industries. In this paper, we provided a set of experiments on the generated foams by carbon dioxide (CO2) and nitrogen (N2), cyclic CO2 injection, water alternating gas injection (WAG), active carbonated water injection (coupling surfactant effects and carbonated water (CW)), and introducing the impact of active carbonated water alternating gas injection (combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…(B) Hybrid CW-surfactant injection (SF: surfactant flooding, ACWI: active CWI, ACWAG: active CW alternating gas). References on the x -axis: 1: ref , 2: ref , 3: ref , 4: ref .…”
Section: Co2 Utilizationmentioning
confidence: 99%
“…(B) Hybrid CW-surfactant injection (SF: surfactant flooding, ACWI: active CWI, ACWAG: active CW alternating gas). References on the x -axis: 1: ref , 2: ref , 3: ref , 4: ref .…”
Section: Co2 Utilizationmentioning
confidence: 99%
“…The synergistic effect of combining surfactants with CW has been demonstrated in our prior core flooding experiments 20,21 and confirmed by other research. 52,53 The increased CO 2 solubility, reduced IFT, and improved wettability resulted in a final recovery of 40 to 64% from the active carbonated water (ACW) injection. 20,21,33,52,53 Karfry et al 54 demonstrated that CLSW improves wettability, increases CO 2 dissolution, and enhances core porosity and permeability through dissolution, similar to the experimental results of Soleiman et al 55 With the synergistic effect of low salinity water and CW, the final recovery of CLSW injection reached 51 to 80.2%.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 The increased CO 2 solubility, reduced IFT, and improved wettability resulted in a final recovery of 40 to 64% from the active carbonated water (ACW) injection. 20,21,33,52,53 Karfry et al 54 demonstrated that CLSW improves wettability, increases CO 2 dissolution, and enhances core porosity and permeability through dissolution, similar to the experimental results of Soleiman et al 55 With the synergistic effect of low salinity water and CW, the final recovery of CLSW injection reached 51 to 80.2%. The results of core flooding experiments by Bakhshi et al 56 and numerical simulations by Lee et al 57 suggest that CLSW can achieve improved CO 2 storage; however, some argue that the reduced salinity of CLSW may be detrimental to CO 2 storage.…”
Section: Introductionmentioning
confidence: 99%
“…The injection patterns that can be applied to the waterflooding method are based on (Thakur G, 2020) [3] as follows: Line drive pattern, 4-spot pattern, 5-spot pattern, 7-spot pattern, 9spot pattern, Peripheral pattern. An experiment conducted by Yang G. et al (2022) [4] , to determine the recovery factor after waterflooding. Reservoir simulation experiments were carried out on foam produced by carbon dioxide (CO2) and nitrogen (N2), cyclic C02 injection, water alternating gas (WAG) injection, active carbonated water injection (combining the effects of surfactants and carbonated water (CW) and introduced impact of alternating gas injection of activated carbonated water (combination of WAG and CW injection) after waterflooding.…”
Section: Introductionmentioning
confidence: 99%
“…The use of carbon dioxide (CO 2 ), nitrogen (N2), cyclic CO, a combination of water and gas (WAG), and active carbonated water injection are also often used. Guilin Yang at.all [12] has conducted research on the use of a combination of water and gas (WAG) as an injection fluid which has succeeded in increasing recovery up to 74% in an oil field. However, in this research, an attempt was made to simulate the use of suspended wells for production wells and injection wells, so that project costs can be reduced more cheaply and more efficiently.…”
Section: Introductionmentioning
confidence: 99%